Expanding the approach of sovereignty: Ecuadorian Armed Forces facing transnational organized crime - Andrade-Vásquez, Miguel (2024)
Ecuadorean Armed Forces have been arguably ineffective in confronting transnational organised crime (TOC). The study argues that this ineffectiveness is due to the adoption of the Westphalian approach, which considers that the objective of the military is the defense of the different territorial dimensions of a State against conventional threats. This approach, still in force in Ecuador's defence policy, is not in tune with new threats such as TOC and related crimes. Based on a historical-conceptual overview and a review of the national defence policy (2002 and 2018), the research concludes that the solution consists not only in a legal and constitutional expansion of the powers of the Armed Forces in the field of public order and internal security, but also in questioning and expanding the approach to sovereignty beyond its classic notions in the face of central threats to the State such as TOC.